1985
DOI: 10.1113/jphysiol.1985.sp015822
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic excitation of neurones in area 17 of the cat by intracortical axon collaterals of cortico‐geniculate cells.

Abstract: SUMMARY1. Antidromic activation of layer 6 cortico-geniculate cells from the lateral geniculate nucleus (l.g.n.) was used to study synaptic effects mediated by their intracortical axon collaterals. A specific stimulation procedure, earlier shown to suppress geniculo-cortical synaptic effects and to enhance synaptic effects from layer 6 cell collaterals was employed to differentiate between inputs from the two pathways. Single cells in different cortical layers were recorded both extra-and intracellularly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…2C), consistent with the literature on TC STPs; the exact amount of depression varied from connection to connection. Depression always reached steady state earlier than 1 s after beginning stimulation, which again is in line with earlier work performed under similar conditions (Gil et al, 1999;Gabernet et al, 2005).…”
Section: Ongoing Stimulation Evokes Diverse Thalamocortical Short-tersupporting
confidence: 80%
See 1 more Smart Citation
“…2C), consistent with the literature on TC STPs; the exact amount of depression varied from connection to connection. Depression always reached steady state earlier than 1 s after beginning stimulation, which again is in line with earlier work performed under similar conditions (Gil et al, 1999;Gabernet et al, 2005).…”
Section: Ongoing Stimulation Evokes Diverse Thalamocortical Short-tersupporting
confidence: 80%
“…For example, PSP width could differ across recordings as a result of variation in intrinsic membrane properties, which would be expected to influence PSP width throughout the train. Another mechanism for broadened PSPs could be shortterm depression of disynaptic inhibition: this would imply increased PSP broadening, and summation, over the course of a stimulus train (Gabernet et al, 2005;Higley and Contreras, 2006). To cover both of these possibilities and to test for an effect of PSP width, PSP broadening, and summation, we measured PSP width as the full-width at half-maximum, both for the first response from rest and the first response after switching to irregular stimulation from steady state.…”
Section: Stp Diversity Has a Monosynaptic Locusmentioning
confidence: 99%
“…This is unlikely because the stimulus threshold for activating thalamocortical (TC) axons is ϳ1 order of magnitude lower than the current required to antidromically activate corticothalamic (CT) cells (Ferster and Lindström, 1985;Stratford et al, 1996;Swadlow, 1998). In addition, previous studies reported that TC and CT axon bundles travel in different anteroposterior planes in the internal capsule, such that slices containing TC afferents rarely include CT axons (Agmon and Connors, 1991;Agmon and Connors, 1992).…”
Section: Thalamic-evoked Activitymentioning
confidence: 96%
“…An alternative interpretation of our results is that our intrathalamic stimulation activated axons of CTNs antidromically and that at least some of the EPSPs we observed in SOMϩ interneurons were mediated by the intracortical collaterals of these axons. Such antidromically mediated EPSPs would appear monosynaptic, would have longer latencies due to the slower conduction velocities of corticothalamic axons (40,41), and would undergo facilitation (32,33). However, FS/PVϩ interneurons also receive facilitating EPSPs from CTNs or CTN-like pyramidal cells (32,33).…”
Section: Thalamus-evoked Epsps Were Not Mediated By Antidromically Acmentioning
confidence: 99%